2018
DOI: 10.2903/j.efsa.2018.5172
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness to set a group health‐based guidance value for fumonisins and their modified forms

Abstract: The EFSA Panel on Contaminants in the Food Chain (CONTAM) established a tolerable daily intake (TDI) for fumonisin B 1 (FB 1 ) of 1.0 lg/kg body weight (bw) per day based on increased incidence of megalocytic hepatocytes found in a chronic study with mice. The CONTAM Panel considered the limited data available on toxicity and mode of action and structural similarities of FB 2-6 and found it appropriate to include FB 2 , FB 3 and FB 4 in a group TDI with FB 1 . Modified forms of FBs are phase I and phase II met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 267 publications
(627 reference statements)
0
41
0
4
Order By: Relevance
“…It should be noted that fumonisin exposure in natural settings for both animals and humans is not purified, and in animal studies the adverse effects on feed consumption and weight gain are often concurrent with other adverse effects such as hepatotoxicity and renal toxicity. The toxicity of fumonisins in laboratory and farm animals has been reviewed extensively (JECFA, , ; Knutsen et al., ; WHO, ). The following is not an all‐inclusive review, as these documents have previously done; but is intended to highlight the specific relationship between fumonisin intake and growth impairment in animals.…”
Section: Fumonisin Exposure and Growth Impairmentmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that fumonisin exposure in natural settings for both animals and humans is not purified, and in animal studies the adverse effects on feed consumption and weight gain are often concurrent with other adverse effects such as hepatotoxicity and renal toxicity. The toxicity of fumonisins in laboratory and farm animals has been reviewed extensively (JECFA, , ; Knutsen et al., ; WHO, ). The following is not an all‐inclusive review, as these documents have previously done; but is intended to highlight the specific relationship between fumonisin intake and growth impairment in animals.…”
Section: Fumonisin Exposure and Growth Impairmentmentioning
confidence: 99%
“…Several recent studies have shown that the residual hydrolyzed forms of fumonisin formed during alkaline hydrolysis are less toxic in animal feeding studies (Grenier et al., ; Voss, Riley, Moore, & Burns, ; Voss, Ryu, Jackson, Riley, & Gelineau‐van Waes, ). These studies and others have been reviewed in the recently published Scientific Opinion of the EFSA (Knutsen et al., ). Dombrink‐Kurtzman, Dvorak, Barron, and Rooney () reported that alkaline treatment can significantly reduce the amount of FB 1 in the process of making tortillas.…”
Section: Interventions For Fumonisin Reductions In Crops and Foodsmentioning
confidence: 99%
See 3 more Smart Citations